Ascending aorta dissection complicated by acute myocardial infarction and cardiogenic shock in a patient with Marfan syndrome - Bugajski, Paweł; Greberski, Krzysztof; Buszkiewicz, Karol; Jarząbek, Radosław; Jedliński, Ireneusz; Kalawski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Ascending aorta dissection including coronary ostia and/or causing severe aortic valve regurgitation can lead to cardiogenic shock. In our case, there was an acute type A aortic dissection, coronary ostia dissection and myocardial infarction leading to cardiogenic shock. Surgical technique and diagnostic methods were adjusted to the dynamicprogress of the disease. Applied treatment resulted in therapeutic success.